Study of polysialated recombinant human insulin - M. N. Korchagnikova; I. V. Nazimov; Yu. M. Glubokov; V. V. Bezuglov (Тонкие химические технологии, 2009)
The method of structure determination of the recombinant glycosylated peptides and proteins has been elaborated by the example of the gene-spliced human insulin.